1991
DOI: 10.1007/bf01974982
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral drugs

Abstract: There are only a limited number of effective, non-toxic antiviral drugs for clinical use, whereas there is a great need for such drugs. Especially for the treatment of patients infected with the human immuno-deficiency virus (HIV) anti-HIV drugs are required. At the same time viral infections secondary to AIDS cannot yet be treated effectively. An increasing problem is the development of virus strains resistant to the available drugs. At this moment a great effort is made in the research for new antiviral drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…This phenomenon is indicated in therapeutic index (TI) showing˃ 25. The TI compares well with the TI value established in acyclovir [45], indicating that the extract could provide useful compounds, if fractionated and identified by bioactivity guided assays. Phytochemical studies has previously reported the presence of; Isomanniflavanone; an ent-eriodictyol-(3a→6)-dihydroquercetinlinked biflavanone, 1,5-dimethoxyajacareubin; depsidone garcinisidone -G; (2"R,3"R)-preussiannon; euxanthone; 2-isoprenyl-1,3,5,6-tetrahydroxyxanthone; jacareubin; isogarcinol and garcinol in ethanolic-aqueous extract of G. buchananii [28].…”
Section: In Vitro Antiviral Activity By Epttsupporting
confidence: 60%
See 2 more Smart Citations
“…This phenomenon is indicated in therapeutic index (TI) showing˃ 25. The TI compares well with the TI value established in acyclovir [45], indicating that the extract could provide useful compounds, if fractionated and identified by bioactivity guided assays. Phytochemical studies has previously reported the presence of; Isomanniflavanone; an ent-eriodictyol-(3a→6)-dihydroquercetinlinked biflavanone, 1,5-dimethoxyajacareubin; depsidone garcinisidone -G; (2"R,3"R)-preussiannon; euxanthone; 2-isoprenyl-1,3,5,6-tetrahydroxyxanthone; jacareubin; isogarcinol and garcinol in ethanolic-aqueous extract of G. buchananii [28].…”
Section: In Vitro Antiviral Activity By Epttsupporting
confidence: 60%
“…The TI was ˃6 and like G. buchananii, there was good cell tolerance as well as favorable comparison with TI of acyclovir [45]. Previous studies have shown that the main constituents of C. decapetala belong to terpenoid and flavonoids [42].…”
Section: Decapetalamentioning
confidence: 87%
See 1 more Smart Citation
“…56 and > 7.13 respectively); indeed, their CC 50 values were not determined, because they had a value > 1000 µg/ ml, in other words they were not cytotoxic. Comparing IC 50 and therapeutic index values for Acyclovir (Wiltink & Janknegt 1991) with the values for the E. cotinifolia and E. tirucalli water-methanol extracts, it can be concluded that these extracts have an acceptable antiviral activity. For this reason the E. cotinifolia and E. tirucalli species are good candidates for further activity-monitored fractionation to identify their active principles.…”
Section: Resultsmentioning
confidence: 96%
“…An analogous situation exists with aciclovir, which is only 15% to 20% bioavailable after oral administration. Efforts have been made to develop an analogue, desciclovir, with better absorption properties [1].…”
Section: Immunomodulationmentioning
confidence: 99%